Interactions between arbuscular mycorrhizal fungi and phosphate-soluble bacteria affect ginsenoside compositions by modulating the C:N:P stoichiometry in Panax ginseng - Mu, Peng; Ding, Guanzhong; Zhang, Yue; Jin, Qiao; Liu, Zhengbo; Guan, Yiming; Zhang, Linlin; Liang, Chijia; Zhou, Fan; Liu, Ning (Frontiers in Microbiology, 2024)
The biomass production as well as the accumulation of secondary metabolites of plant is highly determined by the absorption of nutritional elements, in particular nitrogen (N) and phosphorus (P). Arbuscular mycorrhizal fungi (AMF) can absorb soluble P and transport it to plants, while phosphate solubilizing bacteria (PSB) can increase the content of solubilizing P in soil. Previous studies have identified the effects of either AMF or PSB inoculation on altering plant C:N:P stoichiometry, whether AMF interact with PSB in promoting plant growth and changing elemental concentration and composition of secondary metabolites by altering plant C:N:P stoichiometry remains ambiguous. In this study, we investigated the effects of inoculation of AMF, PSB, and their co-inoculation AMP (AMF and PSB) on the biomass growth, the C: N: P stoichiometry, the core microorganisms of rhizosphere soil, and the ginsenoside compositions of ginseng (Panax ginseng). The results showed that compared to control or single inoculation of AMF or PSB, co-inoculation of AMF and PSB significantly increased the AMF colonization rate on ginseng roots, increased the biomass of both above and under-ground parts of ginseng. Similarly, co-inoculation of AMF and PSB substantially increased the concentrations of N and P, reduced the ratios of C:P and N:P in the above-ground part of ginseng. The co-inoculation of AMF and PSB also increased concentrations of total ginsenosides and altered the compositions of ginsenosides in both the above and under-ground parts of ginseng. Analysis the rhizosphere microorganism showed that the co-inoculation of AMF and PSB recruited distinct core microorganisms that differ from the control and treatments with single inoculation of AMF or PSB. Our results suggested that PSB inoculation enhanced the positive effect of AMF in improving the absorption of nutrimental elements, altered the C:N:P stoichiometry and, ginsenosides concentration and composition of ginseng, influenced the plant rhizosphere microbial community. These findings offer valuable insights into enhancing plant biomass production and promoting secondary metabolites by improving the plant-fungi-bacterial relationships.